Melaço de soja fermentado: produção de ácido gama poliglutâmico (y-PGA) e tratamento de sementes - Silva, Ana Paula Fragoso Corrêa da (2023)
Soy molasses is a co-product of the soy processing industry, and because it is rich in carbon, it can be used as a culture medium for the growth of microorganisms, producing important metabolites, capable of promoting plant development. Gamma-polyglutamic acid (y-PGA) obtained by the microbial fermentation process can increase root biomass and activity, optimizing nutrient absorption and plant yield. The objective was to evaluate the potential of soybean molasses fermented by bacteria of the genus Bacillus for the production of the biopolymer y-PGA and its biostimulant effect in the treatment of corn seeds. The work was conducted in three phases. In phase 1, three strains of Bacillus subtilis (BSA, BSS and BSM), two strains of B. amyloliquefaciens (BAA and BAS) and one strain of B. licheniformis (BLM) were evaluated at different concentrations of total reducing sugar (ART) of soy molasses (28; 56; 112 and 224 g L-1) compared to the standard medium (nutrient broth). Subsequently, the BSA, BAA and BLM strains were selected to be evaluated in two concentrations of ART from soy molasses (28 and 56 g L-1) in comparison with broth E (recommended medium for the production of y-PGA) as to the growth and production of y-PGA and indoleacetic acid (IAA) over eight days of cultivation. In phase 2, the Bacillus strain with the highest production of y-PGA was used to ferment soy molasses and obtain the biostimulant. In phase 3, corn seeds were treated with the filtered and unfiltered biostimulant compared to 56 L-1 ART soy molasses medium and water, to evaluate the germination and initial growth of corn seedlings. Bacillus strains showed greater growth in soy molasses media at concentrations of 28 and 56 g L-1 of ART compared to nutrient broth; the concentration of 224 g L-1 of ART inhibited the growth of the studied strains. The BSA line showed higher growth than the BAA and BLM lines, with greater growth in the 56 g L-1 ART molasses medium. The BSA strain in soy molasses media 28 and 56 g L-1 ART showed greater growth and AIA production compared to broth E. The BAA strain in soy molasses 56 g L-1 ART medium showed the highest y-PGA production compared to BSA and BLM strains. The y-PGA produced by the fermentation of soy molasses 56 g L1 ART fermented by BAA showed purity similar to the synthetic one (y-PGA Sigma®). The biostimulant (soy molasses 56 g L-1 ART fermented by BAA) filtered and unfiltered did not influence the germination and initial development of corn seedlings. Additional studies are needed to evaluate the effects of the biostimulant throughout the development of corn seedlings.